The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1121/1.3238248
|View full text |Cite
|
Sign up to set email alerts
|

A simple single-interval adaptive procedure for estimating thresholds in normal and impaired listeners

Abstract: This report presents a single-interval adaptive procedure for measuring thresholds in untrained normal and impaired listeners. The accuracy of the procedure is evaluated using Monte Carlo methods and human data allowing a method to be proposed for deciding in advance the number of trials required to achieve a specified level of accuracy. The number of trials depends on the slope of the psychometric function. The slope of the psychometric function is evaluated in normal and impaired listeners, and is found to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 21 publications
4
73
1
Order By: Relevance
“…The MLE YN task mostly assumes an underlying psychometric function based on the logistic function (Green, 1990). This assumption has not been found to be robust (e.g., Lecluyse & Meddis, 2009), though Gu and Green (1994) argued this finding away, claiming that because the threshold estimates produced by the procedure are consistent with others reported in the literature, it is a moot point whether these assumptions are upheld. However, Lecluyse and Meddis reported that psychometric functions do differ across clinical groups, and a universal form should not be assumed; this stance was supported by Leek (2001).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The MLE YN task mostly assumes an underlying psychometric function based on the logistic function (Green, 1990). This assumption has not been found to be robust (e.g., Lecluyse & Meddis, 2009), though Gu and Green (1994) argued this finding away, claiming that because the threshold estimates produced by the procedure are consistent with others reported in the literature, it is a moot point whether these assumptions are upheld. However, Lecluyse and Meddis reported that psychometric functions do differ across clinical groups, and a universal form should not be assumed; this stance was supported by Leek (2001).…”
Section: Discussionsupporting
confidence: 52%
“…It soon became apparent after Green's (1990) initial description of the MLE YN task that threshold estimates could be significantly different from those reported in the literature (Green, 1993). Since then, it has been consistently demonstrated (e.g., Baker & Rosen, 2001;Green, 1995;Gu & Green, 1994;Lecluyse & Meddis, 2009;Leek, 2001) that the MLE YN task is extremely unforgiving of errors that occur early in a track, especially in the first five trials (Gu & Green, 1994). Such mistakes are more likely to be made with naive participants than experienced ones, and because of this issue the MLE YN task cannot be relied on to give estimates of true threshold with untrained participants.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A single-interval, adaptive, up-down procedure was used throughout as described and evaluated by Lecluyse and Meddis (2009). Data were collected from eight NH and eight hearing-impaired listeners.…”
Section: Methodsmentioning
confidence: 99%
“…Comparison sounds (pure tones of 250, 500, 1000, 1500, 2000, 3000, 4000, 6000, 8000, 12 000, and 16 000 Hz) were generated using custom-made MATLAB software and were presented via Sennheiser HD600 headphones. The comparison tones were first matched to the loudness of the tinnitus using a singleinterval adaptive procedure (Lecluyse and Meddis, 2009). During loudness matching, sound intensity was limited to levels 100 dB SPL.…”
Section: Tinnitus Spectrum Measurementsmentioning
confidence: 99%